Collaborative Learning in Elementary Science Supported by Learning by Inquiry and Augmented Reality (International Conference on Computers in Education, 2017)
The significance of science in the development of technology is undeniable and had proven its importance in the advancement of today’s technology. Hence it had result in the strong emphasis of science in the educational field. Elementary science consists of having students learning and understanding scientific concepts and knowledge. With the teacher-centered teaching method commonly adopted in schools, it would be difficult for students to fully understand and apply the learnt concepts and knowledge in real life. This research designed an application that utilized collaborative learning in the learning process, allowing students to solve problems by discussing with peers through the strategy of learning by inquiry by working on hands-on activities in augmented campus environments. The results of this research found that collaborative learning supported by learning by inquiry and augmented reality technology had positive impact on the learning performance of students in the subject of science.